GENERALIZED ENTROPY METHOD FOR THE RENEWAL EQUATION WITH MEASURE DATA - Gwiazda, Piotr; Wiedemann, Emil (Communications in Mathematical Sciences, 2017)
We study the long-time asymptotics for the so-called McKendrick-Von Foerster or renewal equation, a simple model frequently considered in structured population dynamics. In contrast to previous works, we can admit a bounded measure as initial data. To this end, we apply techniques from the calculus of variations that have not been employed previously in this context. We demonstrate how the generalized relative entropy method can be refined in the Radon measure framework.
CRIS-Team Scopus Importer:2023-01-17
Keywords: concentration measure; generalized relative entropy methods; measure-valued solutions; positive Radon measures; Structured population model